What Level of Public Debt Could India Target? - Topalova, Petia (IMF Working Papers; Working Paper ;, 2010)
This paper discusses possible medium-term public debt targets for India, based on evidence from the economic literature on prudent levels of public debt and the feasibility for the country to meet a particular target over the next 5-6 years. While recognizing the challenges in determining an appropriate debt target, cross-country analysis and simulations suggest that a debt ratio in the range of 60-65 percent of GDP by 2015/16 might be suitable for India. Such a debt ceiling, while still above the average debt level for emerging markets, is within the range of debt ratios that would provide room for countercyclical fiscal policy and contingent liabilities. It would also send a strong signal of the government's commitment to fiscal consolidation by making a clear break with the past.